Cichorium intybus Roots Extract: A New Culture Medium for Cultivation of Aspergillus niger, Aspergillus terreus, Fusarium graminearum and Candida albicans - Fitua Minuar Aziz (College of Pharmacy / Mustansiriyah University, 2014)
For the first time globally, the studying of using hot water extract of Cichorium intybus (chicory) as a new culture medium for fungi and yeast growth was done .It used for cultivation of: Aspergillus niger ,Aspergillus terreus,Fusarium graminearum and Candida albicans. The present study clearly showes the possibility of using the chicory roots extract agar medium as a new culture medium for molds and yeasts. The results showed avariation in the growth of fungi on chicory roots extracts agar medium compared with potato dextrose agar medium (PDA) in colony growth diameter mean ,colony color, sporulation and producing of different color dyes. The sporulation for Aspergillus niger and Aspergillus terreus was heavy on chicory roots extract agar medium compared with PDA medium. In addition,the prepared medium will be usefull for fungal toxomony,for Aspergillus terreus and Fusariun graminearum, dark yellow pigment of Aspergillus terreus on chicory medium while it was yellow pigment on PDA. Fusarium gramiearum produce purple color pigment on chicory medium while it was pink pigment on PDA,also chicory medium was good medium for cultivation of Candida albicans without producing pigments.